Fresh Osteochondral Allograft Transplantation for Osteochondritis Dissecans of the Knee - Sadr, Kamran N. (Orthop J Sports Med, 2014)
OBJECTIVES: Osteochondritis dissecans (OCD) of the knee can be difficult to treat. Cartilage restoration techniques are often indicated when the lesion or fragment cannot be salvaged. Fresh osteochondral allograft (OCA) transplantation can restore both bone and cartilage defect as a treatment modality. We hypothesize that osteochondral allografting is a successful method for treating osteochondritis dissecans of the knee. METHODS: Between 1983 and 2010, 164 patients (181 knees) underwent OCA for OCD of the femoral condyle(s) (type III or IV). Minimum two-year follow-up was available on 149 patients (165 knees). Median age was 25 years (range, 14 to 55) and 73% were male. Mean allograft size was 7.2 cm(2)(range, 2 to 23 cm(2)). Evaluation included frequency and type of reoperations, modified Merle d’Aubigné-Postel (18-point) scale, International Knee Documentation Committee (IKDC) pain and function scores, and Knee Society function (KS-F) score. Clinical failure was defined as revision OCA or conversion to arthroplasty. Graft survivorship was determined. RESULTS: Median follow-up time was 7.7 years (range, 2 to 28.4 years). 78% had more than 5-year follow-up. Fifty-one of 165 knees (31%) had reoperations, of which 21 (13%) were classified as allograft failures (13 OCA revisions, 5 UKA, and 3 TKA). OCA survivorship was 93% at 5 years, 87% at 10 years, and 77% at 20 years. Of the 144 knees whose grafts were still in situ, 91% were rated good/excellent, 8% were rated fair, and 1% was rated poor. Mean modified Merle d’Aubigné-Postel (18-point) scale was 17, mean IKDC pain and function scores were 2 and 8, and mean KS-F score was 93. 88% of patients reported satisfaction. CONCLUSION: Osteochondral allograft transplantation was an effective treatment for osteochondritis dissecans of the knee, with significant improvement in pain and function scores and high patient satisfaction. Graft survivorship was 87% at 10 years.